The Effect Of Return On Asset, Return On Equity, Earning Per Share, And Price Earning Ratio Toward Stock Return (Empirical Study Of Transportation) - et. al., Mochamad Kohar Mudzakar, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
This study aims to determine the effect of return on asset, return on equity, earnings per share, and price earning ratio on stock returns. The research method used in this research is explanatory. The data used is secondary data. The population in this study are all transportation sub-sector companies listed on the Indonesia Stock Exchange in the 2015-2018 period. Sampling uses a purposive sampling method, so that a sample of 12 companies is obtained with a total of 48 data observations. The data analysis method uses panel data analysis and data testing is done using the Eviews 10 program. The results showed that partial return on asset and earnings per share had no effect on stock returns, whereas return on equity and price earnings ratios had an effect on stock returns, Simultaneously return on asset, return on equity, earnings per share, and price earnings ratio effect on stock returns.